An Analysis of Translation Strategies for English Idiomatic Expressions in the Film Elemental: Force of Nature - Ayu Rachmadini, Ekha Novi; Ana, I Wayan; Pratama, Agus Darma Yoga (JALL (Journal of Applied Linguistics and Literacy), 2025)
The title of this research is Translation Strategies of English Idiomatic Expression in Elemental: Force of Nature movie. This research aimed at discuss about types of idiomatic expression and strategies used by the translator to translate “Elemental: Force of Nature” movie subtitle. The method used in the research was descriptive qualitative method. This study was carried out on fifteen idioms found in the subtitle Elemental: Forces of Nature movie. These idioms were analyzed using McCharty and O’Dell’s (2011) types of idioms theory and Baker’s (1992) strategies for translating idioms. The result of this research showed that: Firstly, there are five types of idioms found in the subtitle. However, idiom type prepositional phrases were the most used idiom types. There are 5 prepositional phrases, 4 idioms type verb + object, 2 compound idiom, 2 simile and 2 whole clause and sentence whereas the idioms types of binomials and trinomial was documented as non-applicable types of idioms. The researcher found all the types of idiomatic translation strategy, they are 2 translation using similar meaning and form, 2 translation similar meaning but dissimilar form, 1 translation by paraphrase and 1 translation by omission.